Antibacterial, hydrophobic, and dyeable homogeneous flame-retardant regenerated cellulose fiber - Guangming Sun; Shuai He; Tian Li; Fayu Sun; Hui Xu; Hejun Li; Jieyu Wei; Guangxian Zhang (Carbohydrate Polymers, 2026)

Lightweight and multifunctional SiC aerogel with hollow microtube-nanowire hybrid structure for thermal shielding and electromagnetic wave absorption - Haiyang Li; Leilei Zhang; Xuemin Yin; Mengjiao Li; Boshi Song; Houbu Li; Hejun Li (Chemical Engineering Journal, 2026)

Soil health index–based assessment of cadmium ecological risk–fertility coupling in seasonally frozen agricultural soils - Haoqin Yang; Haibing Wang; Hejun Zuo; Shichao Chen; Xiya Liu; Chengxian Liao; Xue Chen; Xu Liu; Siqi Li (Journal of Hazardous Materials, 2026)

Tectonic controls and earthquake response of thermal fluid geochemistry in southern Yunnan, southeastern Tibetan Plateau - Chenhua Li; Xiaocheng Zhou; Miao He; Zhaojun Zeng; Yuwen Wang; Jiao Tian; Yucong Yan; Bingyu Yao; Hejun Su; Ruigang Li (Geothermics, 2026)

Quantitative resolution analysis in seismic imaging: From classical theory to cutting-edge advances - Jidong Yang; Jianping Huang; Hejun Zhu; Jiaxing Sun; Li-yun Fu; George McMechan; Houzhu Zhang; Ru-Shan Wu (Earth-Science Reviews, 2026)

Integrating lewis acid/base pairs and hydroxyfunctional groups as dual adsorption sites into porous biochar fiber for enhanced iodine capture - Hongquan Fu; Xiao Wang; Liping Li; Zhenyang Li; Jinming Chang; Fang Liao; Hejun Gao; Juan Zhang; Yunwen Liao (Journal of Water Process Engineering, 2025)

Unraveling structure-2e− ORR selectivity correlations in oxygen-doped carbon catalysts: Defects and carboxyl groups as dual active sites for enhanced H2O2 electrosynthesis and wastewater decontamination - Fangyuan Liu; Zhonghui Han; Lijuan Li; Xianchuan Li; Chunpeng Zhang; Hejun Ren (Chemical Engineering Journal, 2025)

Architectural design of multidimensional carbonaceous structures: Synergistic pathways enabling high-energy silicon-based anodes - Wendi Chen; Lingjun Guo; Ruonan Zhang; Guangyao Liu; Yue Ma; Dian Jia; Hejun Li; Keyu Xie (Chemical Engineering Journal, 2025)

Advancements in antibiotic degradation via electro-activation of peroxymonosulfate with modified carbon materials: A critical review of fundamentals, performance, and future studies - Lijuan Li; Fangyuan Liu; Hejun Ren (Journal of Water Process Engineering, 2025)

Photovoltaic efficiency enhancement via responsive forced convection driven by radiative-cooling-intensified thermoelectricity - Xintao Xie; Yue Liu; Yipeng Zhang; Hongxiang Xie; Jianyong Ye; Hejun Li; Weifan Chen (Chemical Engineering Journal, 2025)

A hydrophobic cathode design towards high-stability Zn-air batteries: Coupling FeTAP molecules with self-supporting edge-rich graphene membrane - Jiachen Meng; Yulei Zhang; Xuemin Yin; Yanqin Fu; Dan Wen; Qiang Song; Hejun Li (Chemical Engineering Journal, 2025)

Construction of oxygenated porous biochar by dual activation method for highly efficient removal of tetracycline from aqueous solution - Jiaxin Hu; Bingyuan Huang; Baoyu Li; Hongquan Fu; Juan Zhang; Hejun Gao; Yunwen Liao (Journal of Water Process Engineering, 2025)

Molecular cloning, expression and functional analysis of foxl2 from Chinese sturgeon (Acipenser sinensis) in relation to sex differentiation - Yacheng Hu; Ruihua Tan; Yang Li; Tingting Shu; Gang Yang; Zhong Chu; Haoran Wang; Xueqing Liu; Xin Zhu; Binzhong Wang; Baifu Guo; Runqiu Wang; et al. (Frontiers in Marine Science, 2024)
Introduction Our understanding of the regulatory mechanisms that govern the development of sexual characteristics in sturgeon, particularly the Chinese sturgeon (Acipenser sinensis), is limited. Foxl2, a member of the forkhead/HNF-3-related transcription factor family, is known for its role in precise gene regulation within specific tissues and its control over ovarian aromatase, a key enzyme in ovarian development and maturation. This study aimed to investigate the sexually dimorphic expression of foxl2 during the molecular and morphological sex differentiation stages in Chinese sturgeon. Methods We successfully isolated the full-length cDNAs of foxl2 in Chinese sturgeon. We then examined the expression profiles of this gene across various somatic tissues in both female and male specimens. Results Foxl2 was predominantly expressed in the ovulatory organs of two-year-old Chinese sturgeon, with significantly lower expression in other somatic tissues. We observed sexual dimorphism in foxl2 expression within gonads that had achieved morphological differentiation. Discussion The results suggest that foxl2 expression is intricately linked to the process of ovarian differentiation in Chinese sturgeon. Furthermore, we propose that the mRNA quantities of foxl2 could serve as an accurate biomarker for sex determination in sturgeon during their early growth stages.

Dynamics of Haptophytes (Eukaryota, Hacrobia) Revealed via Short-Term Sampling in the South China Sea - Haoyue Zhang; Ran Li; Bowei Gu; Hejun Kong; Jie Xu; Rui Zhang; Xiaolin Li; Nianzhi Jiao; Dapeng Xu (Journal of Ocean University of China, 2024)

Multifunctional 3D pristine graphene with tunable electromagnetic properties via self-assembly strategy - Yuan Ma; Lingjun Guo; Lehua Qi; Yuchen Cao; Hejun Li (Chemical Engineering Journal, 2024)

Multiphase ceramic SiBCN-ZrO2/ZrC/ZrB2/SiC with ultra-wide bandwidth electromagnetic absorption - Qian Wang; Yumeng Deng; Mengyu Dai; Yujun Jia; Hejun Li (Chemical Engineering Journal, 2024)

Cloning, identification, and functional analysis of foxl2 gene and its expression after 17β‐estradiol (E2) treatment in Dabry’s sturgeon, Acipenser dabryanus - Yacheng Hu; Ruihua Tan; Tingting Shu; Zhong Chu; Haoran Wang; Yining Chen; Xin Zhu; Yang Li; Binzhong Wang; Baifu Guo; Runqiu Wang; Huantao Qu; et al. (Frontiers in Marine Science, 2024)
The study focuses on the critically endangered Dabry’s sturgeon ( Acipenser dabryanus ), a species on the brink of extinction in the wild. This research investigates the role of the Forkhead box protein L2 ( foxl2 ) in the gonadal development and differentiation of this species. The foxl2 gene, known for its role in various physiological processes, including sexual maturation, is hypothesized to play a significant role in the sex differentiation of Dabry’s sturgeon. This study cloned the full-length cds sequence of the foxl2 gene and analyzed its expression across various tissues, focusing on its response to estradiol treatment. Our findings indicate that foxl2 is predominantly expressed in ovaries and shows a dose-dependent response to estradiol, suggesting its potential role in ovarian differentiation. This research underscores the importance of foxl2 in understanding reproductive biology and offers a foundation for future conservation strategies.

Development and characterization of pH-sensing films based on red pitaya (Hylocereus polyrhizus) peel treated by high-pressure homogenization for monitoring fish freshness - Hejun Wu; Luhong Chen; Ting Li; Shasha Li; Yanlin Lei; Maoxu Chen; Saiyan Chen; Xiangyang Yuan; Zhiqing Zhang; Anjun Chen (Food Hydrocolloids, 2024)

Enhancement of thermal–mechanical performances via a selective CNTs configuration in laminated CNTs/AZ31B composite - Qian Zhang; Jiawei Fu; Jiming Zhou; Lehua Qi; Hejun Li (Chemical Engineering Journal, 2024)

Enhanced capacitive deionization for Cr(VI) removal from electroplating wastewater: Efficacy, mechanisms, and high-voltage flow electrodes - Rui Zhou; Jingyang Li; Yunbo Dai; Fangyuan Liu; Shuzheng Yang; Hejun Ren; Chunpeng Zhang (Journal of Environmental Chemical Engineering, 2024)

Pectin mediates the mechanism of host blood glucose regulation through intestinal flora - Qing Guo; Xiaoyan Hou; Qiang Cui; Shanshan Li; Guanghui Shen; Qingying Luo; Hejun Wu; Hong Chen; Yuntao Liu; Anjun Chen; Zhiqing Zhang (Critical Reviews in Food Science and Nutrition, 2024)

Eggshell powder as a bio-filler for starch and gelatin: Ternary biodegradable composite films manufactured by extrusion compression molding - Ting Li; Ruofei Li; Haodan Luo; Lu Peng; Jie Wang; Shasha Li; Man Zhou; Xiangyang Yuan; Zhiqing Zhang; Hejun Wu (Food Hydrocolloids, 2024)

Robust micro-nano hybrid aerogel derived from waste resources for thermal management and high-efficiency adsorption - Shanshan Ma; Hejun Li; Jie Fei; Qiyue Huang (Chemical Engineering Journal, 2024)

The dissolution characteristics of cadmium containing birnessite produced from paddy crusts - Liang Peng; Dan Li; Huijuan Song; Xiaolin Kuang; Qingru Zeng; Hejun Ao (Science of The Total Environment, 2024)

The swelling induced choline alkali-urea (SICAU) process for sustainable crop straw upgrading - Yuehan Jiang; Feiyue Shen; Baiheng Jiang; Yuheng Hu; Jinguang Hu; Mei Huang; Li Zhao; Hejun Wu; Dong Tian; Fei Shen (Chemical Engineering Journal, 2024)

Achieving broadband electromagnetic absorption at a wide temperature range up to 1273 K by metamaterial design on polymer-derived SiC-BN@CNT ceramic composites - Bin Ren; Yumeng Deng; Yujun Jia; Liyuan Han; Xin Wang; Hejun Li (Chemical Engineering Journal, 2023)

Evaluation of the impact of moral dissonance-based low-carbon interventions on consumer behavior - Li Xue; Chaoran Li; Endi Cai; Wenqing Wan; Shuo Wei; Zhuo Yu; Hejun Xu (Journal of Cleaner Production, 2023)

Evaluation of the cytotoxic activity of triphenyl phosphate on mouse spermatocytes cells - Yixing Feng; Jiachen Shi; Ming Li; Hejun Duan; Bing Shao (Toxicology in Vitro, 2023)

Geochemical precursory characteristics of soil gas Rn, Hg, H2, and CO2 related to the 2019 Xiahe Ms5.7 earthquake across the northern margin of West Qinling fault zone, Central China - Huiling Zhou; Hejun Su; Chenhua Li; Yue Wan (Journal of Environmental Radioactivity, 2023)

Heterogeneous stacking strategy towards carbon aerogel for thermal management and electromagnetic interference shielding - Liyuan Han; Kezhi Li; Huimin Liu; Yameng Jiao; Xuemin Yin; Hejun Li; Qiang Song; Lehua Qi (Chemical Engineering Journal, 2023)

Development and characterization of antioxidant composite films based on starch and gelatin incorporating resveratrol fabricated by extrusion compression moulding - Hejun Wu; Ting Li; Lu Peng; Jie Wang; Yuixiao Lei; Shasha Li; Qingye Li; Xiangyang Yuan; Man Zhou; Zhiqing Zhang (Food Hydrocolloids, 2023)

Sustained-release antibacterial gelatin films: Effects of diatomite/carvacrol complex on their structure, physicochemical and antibacterial properties - Hejun Wu; Ling Ma; Sen Li; Jie Wang; Ting Li; Lu Peng; Shasha Li; Qingye Li; Xiangyang Yuan; Man Zhou; Zhiqing Zhang; Yuntao Liu (Food Packaging and Shelf Life, 2023)

Hydrogenation of dimethyl oxalate to ethanol over Mo-doped Cu/SiO2 catalyst - Zheng Li; Yihui Li; Xuepeng Wang; Yuan Tan; WenShao Yang; Hejun Zhu; Xingkun Chen; Wei Lu; Yunjie Ding (Chemical Engineering Journal, 2023)

A systematic review of electrocoagulation technology applied for microplastics removal in aquatic environment - Fangyuan Liu; Chunpeng Zhang; Huilin Li; Nnanake-Abasi O. Offiong; Yuhang Bi; Rui Zhou; Hejun Ren (Chemical Engineering Journal, 2023)

Transcriptomics for Drought Stress Mediated by Biological Processes in-relation to Key Regulated Pathways in Gossypium darwinii - Cuilian Xu; Muhammad Kashif Ilyas; Richard Odongo Magwanga; Hejun Lu; M Kashif Riaz Khan; Zhongli Zhou; Yujun Li; Zhengcheng Kuang; Asif Javaid; Danish Ibrar; Abdul Ghafoor; Kunbo Wang; et al. (Molecular Biology Reports, 2022)

Correction to: Mitigating Velocity Errors in Least-Squares Imaging Using Angle-Dependent Forward and Adjoint Gaussian Beam Operators - Jidong Yang; Jianping Huang; Zhenchun Li; Hejun Zhu; George McMechan; James Zhang; Yang Zhao (Surveys in Geophysics, 2022)

Mitigating Velocity Errors in Least-Squares Imaging Using Angle-Dependent Forward and Adjoint Gaussian Beam Operators - Jidong Yang; Jianping Huang; Zhenchun Li; Hejun Zhu; George McMechan; James Zhang; Yang Zhao (Surveys in Geophysics, 2021)

Genomic Selection Using BayesCπ and GBLUP for Resistance Against Edwardsiella tarda in Japanese Flounder (Paralichthys olivaceus) - Yang Liu; Sheng Lu; Feng Liu; Changwei Shao; Qian Zhou; Na Wang; Yangzhen Li; Yingming Yang; Yingping Zhang; Hejun Sun; Weiwei Zheng; Songlin Chen (Marine Biotechnology, 2018)

Oxidative removal of metronidazole from aqueous solution by thermally activated persulfate process: kinetics and mechanisms - Rui Zhou; Tingting Li; Yu Su; Taigang Ma; Lijian Zhang; Hejun Ren (Environmental Science and Pollution Research, 2018)

Correlations between soil gas and seismic activity in the Generalized Haiyuan Fault Zone, north-central China - Huiling Zhou; Hejun Su; Hui Zhang; Chenhua Li (Natural Hazards, 2017)

Molecular cloning, mapping, and tissue expression of the porcine cluster of differentiation 14 (CD14) gene - Xiao-Tian Qiu; Yu-Hua Li; HeJun Li; Ying Yu; Qin Zhang (Biochemical Genetics, 2007)